2022
DOI: 10.1016/j.jss.2021.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Laparoscopic Pyloromyotomy for Pyloric Stenosis—A Systematic Review and Meta-Analysis

Abstract: Introduction: Infantile hypertrophic pyloric stenosis is treated by either open pyloromyotomy (OP) or laparoscopic pyloromyotomy (LP). The aim of this meta-analysis was to compare the open versus laparoscopic technique. Methods: A literature search was conducted from 1990 to February 2021 using the electronic databases MEDLINE, Embase, and Cochrane Central Register of Controlled Trials. Primary outcomes were mucosal perforation and incomplete pyloromyotomy.Secondary outcomes consisted of length of hospital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In the present study, no severe postoperative complications were documented in either of the approaches. The overall postoperative complication rate of LP in our cohort was 7.8%, which was comparable to that in previous studies [ 8 , 21 , 23 ]. When comparing the rate of the most common postoperative complication, our results are equivalent to others, with a rate of 4.7% for wound infection in our cases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, no severe postoperative complications were documented in either of the approaches. The overall postoperative complication rate of LP in our cohort was 7.8%, which was comparable to that in previous studies [ 8 , 21 , 23 ]. When comparing the rate of the most common postoperative complication, our results are equivalent to others, with a rate of 4.7% for wound infection in our cases.…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, wound infection, fascial dehiscence and omental herniation are frequently reported postoperative complications. Previous studies found that there were no significant differences in the postoperative complication rate between open and laparoscopic pyloromyotomy [ 18 , 21 ]. In the present study, no severe postoperative complications were documented in either of the approaches.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown, pyloromyotomy is a procedure with a low rate of complications and mortality for either technique. Until now, there is no clear advantage of the minimal invasive surgery, but also no clear disadvantage ( 16 , 34 ). Open pyloromyotomy can be considered the conventional standard procedure, which is usually performed by residents or even by general surgeons.…”
Section: Discussionmentioning
confidence: 99%